Model Komunikasi Penanganan Kekerasan Seksual terhadap Perempuan dan Anak di Lebak, Banten - Wati, Lina; Jefri, Suci Emelsi; Sari, Nur Musvita (Jurnal Cyber PR, 2025)
This study examines communication models in handling sexual violence against women and children in Lebak Regency, Banten Province. Cases of sexual violence against women and children have been increasing annually. Data collection was conducted through in-depth interviews, observation, and documentation studies. Data analysis was based on case studies and utilized the Nvivo 12 measurement tool. This study revealed that the communication model used in handling sexual violence against women and children involves coordination, direct communication, or the use of telephone or WhatsApp technology, with various UPTD PPA partners, such as the Health, Law, and Police Departments, the Social Service, and the Village Office. The case resolution system and services provided by the UPTD PPA are conducted directly. The first steps in handling cases include public complaints, victim outreach, case management procedures, temporary shelter, and victim assistance. The research recommendations include transitioning to digital platforms, improving infrastructure and training, community education and public awareness, policy implementation, and stakeholder collaboration. Additionally, suggestions include social ecology theory and a bystander intervention model.